Harmonisation of contract law in the EU: Analysis of the process and its impact on the legal system of the Member States - Viktoriia ANATIICHUK; Iryna BANASEVYCH; Ruslana HEINTS; Uliana GRYSHKO (Revista Jurídica Portucalense)
The problem of differences between national legal systems in the global context necessitates the creation of new methods of harmonisation and unification of legislation, especially in light of the accelerating globalisation processes. In the context of global and European integration, it is becoming increasingly important to promote the diversity of jurisdictions and provide answers to the main questions regarding the development of uniform contract law to preserve the role of law as a regulator of social relations at the supranational level. The following methods were used in the study: legal modelling, inductive, deductive, dialectical, formal-logical, and synergistic, as well as methods of analysis and synthesis. The purpose of the article is to analyse the process of harmonisation of contract law in the European Union and to determine its impact on the legal system of the Member States.